Analisis Pengendalian Mutu Sekolah Dalam Meningkatkan Hasil Belajar - Rosnelly Barus; Nordianus Wilfridus; Izza Mutia Raihan; Unifah Rosyidi; Muh. Takdir (Departement of Mathematics Education, 2025)
School quality control is a strategic step in ensuring the achievement of educational standards aimed at improving students' learning outcomes. This article aims to analyze the approaches, supporting factors, and impacts of school quality control on learning outcomes through a literature review. Quality control encompasses processes such as setting standards, monitoring, evaluation, and continuous improvement involving various elements, including school leadership, teacher competence, learning facilities, and parental involvement. The findings indicate that effective implementation of quality control contributes to enhanced student engagement, academic achievement, and character development. Therefore, school quality control plays a crucial role in realizing sustainable quality education